Enhancing NBN's Value: Comparing NBN with Australia’s Top 10 Trading Partners and OECD - Ferrers, Richard Anthony (Journal of Telecommunications and the Digital Economy, 2020)
The NBN, Australia’s National Broadband Network, is nearing its 2020 completion. The value of the NBN depends on what you compare it to. While Australia’s broadband has significantly improved over the last ten years, it is useful to compare Australia’s NBN with similar activity in the OECD and with Australia’s Top 10 Trading Partners to gain a richer understanding of NBN’s value. Australia’s broadband performance compares poorly with other OECD countries on download speed, especially over 100 Mbps download subscriptions and average download speed. However, imminent release in May 2020 of new NBN gigabit pricing could significantly improve Australia’s world ranking on this average download speed comparison. Recommendations for improving NBN’s value beyond speed are made, including encouraging affordable gigabit NBN services; ongoing NBN upgrades; encouraging NBN use; focussing NBN Corporate Reporting on customer satisfaction and ongoing international comparison.